"Factory Outlet" Budaya Produksi dan Produksi Budaya - Muljadi, Hianly (Wacana, Journal of the Humanities of Indonesia, 2002)
This article examines factory outlet as a cultural phenomenon in Indonesia. It specifically focuses in the shift in FO meanings. Through observation, bibliographic study and critical critique, it is shown that FO has been perceived differently from a place to get "branded products" for the lower middle class in order to increase their social status to a shopping heaven for the upper class